Crosstalk of Abscisic Acid with Other Hormones and Signaling Molecules in Tomato Cold Stress Tolerance - Fei Ding; Xiulan Fan; Rongrong Tian; Meiling Wang; Zhihong Sun (Horticulturae, 2025)
Cold stress adversely impacts tomato (Solanum lycopersicum) production, particularly in temperate regions, by impairing growth, development, and yield. Abscisic acid (ABA), a key phytohormone, plays a central role in mediating tomato’s response to cold stress through a complex crosstalk network with other hormones and signaling molecules. This review examines ABA’s interactions with hormones such as ethylene, jasmonates, auxin, gibberellins, salicylic acid, brassinosteroids, and strigolactones, as well as signaling molecules like hydrogen peroxide, nitric oxide, hydrogen sulfide, and calcium. These interactions regulate various physiological processes, including osmolyte accumulation, membrane stability, and oxidative stress mitigation, and influence the expression of cold-responsive genes, such as CBFs, COR, and LEA. Critical knowledge gaps remain, particularly in understanding ABA’s context-specific interactions with other hormones and the integration of calcium signaling with ABA pathways under cold stress. By synthesizing current research, this review enhances our understanding of tomato’s cold stress response and provides insights for genetically improving cold tolerance, supporting sustainable tomato production amid climate challenges.